TINGKAT LITERASI KEUANGAN MAHASISWA UNIVERSITAS DARMA PERSADA DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Hasri Nirmala Budiarti; Puji Rahayu Setyaningsih (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2021)
The purpose of this research is to find out the level of financial literacy of students at Darma Persada University. This research is a quantitative descriptive study that uses a population of all students of the Faculty of Economics at Darma Persada University Jakarta. The sampling technique was carried out by purposive sampling. Data were collected through questionnaires distributed and analyzed using descriptive statistics and multiple regression analysis. The financial literacy of Darma Persada University students is in the good category. The results showed that age, sex and education, partially had no effect on the financial literacy. While the income variable affects the financial literacy variable Simultaneously, the age, gender, education and income variables affect the financial literacy variable.